Antibacterial Effectiveness of Beetroot (Beta vulgaris L.) Juice as an Alternative to Eosin for the Quality of Soil-Transmitted Helminth Egg Examination - Yunita Nurmalasari; Ikhsan Mujahid; Dita Pratiwi Kusuma Wardani; M. Luthfi Almanfaluthi (Jurnal Kesehatan Cendikia Jenius, 2025)
The 2% eosin reagent is commonly used in Soil Transmitted Helminth (STH) egg examination; however, its high cost, toxicity, and poor storage stability highlight the need for safer, natural-based alternatives. This study aimed to evaluate the effectiveness of beetroot (Beta vulgaris L.) juice as a substitute for eosin in staining STH eggs. A true experimental design with a post-test only control group was employed, consisting of six groups: one positive control (2% eosin) and five treatment groups using beetroot juice at concentrations of 40%, 50%, 60%, 80%, and 100%, with 11 preparations per group. Data collection was conducted through microscopic observation in July–August 2025 and analyzed using the Kruskal-Wallis test followed by the Mann-Whitney U post hoc test. The findings revealed significant differences in staining effectiveness (p = 0.027), with the 60% and 100% concentrations showing the best clarity and completeness of egg morphology. The study concludes that beetroot juice is an effective natural alternative to eosin. Further research is recommended to assess storage stability and explore other eco-friendly natural dyes.